2001
DOI: 10.1562/0031-8655(2001)074<0126:cpibhi>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Photodestruction Induced by Hypericin in AY-27 Rat Bladder Carcinoma Cells

Abstract: In a recent clinical study we showed that hypericin accumulates selectively in urothelial lesions following intravesical administration of the compound to patients. In the present study the efficacy of hypericin as a photochemotherapeutic tool against urinary bladder carcinoma was investigated using the AY-27 cells (chemically induced rat bladder carcinoma cells). The uptake of hypericin by the cells increased by prolonging the incubation time and increasing the extracellular hypericin concentration. Photodyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 26 publications
1
21
0
1
Order By: Relevance
“…In contrast to PpIX, hypericin is very photostable 21 and laboratory studies have indicated that, when activated by artificial light, it has enhanced antitumour activity. [22][23][24] Moreover, tests investigating the topical application of hypericin have shown promising results. 13 These results suggest that hypericin may provide a therapeutic benefit when targeted to certain skin diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to PpIX, hypericin is very photostable 21 and laboratory studies have indicated that, when activated by artificial light, it has enhanced antitumour activity. [22][23][24] Moreover, tests investigating the topical application of hypericin have shown promising results. 13 These results suggest that hypericin may provide a therapeutic benefit when targeted to certain skin diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This method has been used in analogous fashion to the extraction of the lipophilic enzymatic product formazan compound from cells, which is part of the standard MTT assay. Another study used 4% sodium dodecyl sulfate in PBS for hypericin extraction (26). In the case of 5 phi' hypericin ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Addition of the singlet oxygen quencher L-histidine was able to prevent the induction of apoptosis by Hyp PDT in AY-27 rat ladder carcinoma cells, whereas necrotic cell death was still feasible at higher PDT doses [114]. These findings point out to the possibility of singlet oxygen having specific signaling functions in the induction of apoptotic cell death (prevented by addition of L-histidine) [64]; however, it is also possible that this substance is able to neutralize singlet oxygen and prevent subsequent ROS formation at concentrations suitable for apoptosis induction, but -over a certain singlet oxygen threshold -fails to prevent severe cellular damage by ROS, resulting in necrosis.…”
Section: Hypericin-based Photocytotoxicity -Apoptosis Versus Necrosismentioning
confidence: 99%
“…From that point on, numerous works studied the mechanistic details of apoptosis induced by Hyp PDT using various model systems [85,[112][113][114][115][116][117][118][119][120][121]. A light-or drug dose-dependent transition from apoptosis to necrosis following Hyp PDT was found in human and murine cancer cell lines by the research groups of Agostinis and de Witte [114][115][116]. As discussed in [64] the final intracellular concentration of Hyp and / or the light dose applied most probably account for the different modes of cell death eventually induced.…”
Section: Dose-dependency Of the Cell Death Mode Induced By Hyp Pdt Cementioning
confidence: 99%